Adolescents’ learning of civics in linguistically diverse classrooms: A thematic literature review - Rinnemaa, Pantea (JSSE - Journal of Social Science Education, 2023)
Purpose: This article explores the interrelationship between second-language students’ literacy development and civics learning in studies focusing on L2 students’ civics learning. Design/methodology/approach: The conceptual framework and the analytical tool in this thematic literature review consists of a four-field model in which the four key components of a. literacy abilities, b. disciplinary literacy abilities, c. prior knowledge, and d. content-area knowledge are in focus. Findings: It is suggested that an interaction between the four components (a-d) could support the students’ civics learning and literacy development. Civics teachers play a crucial role in making the content knowledge comprehensible. Second-language students’ language- and content-related difficulties are better understood in connection to the civics tasks and activities that they work with in civics classrooms. Practical implications: This article addresses issues of continuous education in civics for teachers in L2 civics classrooms.